Euthanasia in the Context of Croatian Healthcare System, Legislation and Bioethical Discussions - Jurić, Hrvoje, filozof (2011)
The aim of this article is to contextualize and discuss the regulation of euthanasia in Croatian ethical and legal codes (Code of Medical Ethics and Croatian Criminal Code), as well as the presence of this issue in scientific and public discussions in Croatia, including media. In that sense, the author firstly explains why euthanasia is one of the key problems of bioethics, mentioning some basic issues in the debate on euthanasia.
Projekt MZOS
ENG